1996
DOI: 10.1042/bj3180111
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of nitrogenase MoFe protein from the mutant strain pHK17 of Klebsiella pneumoniae in which the two bridging cysteine residues of the P-clusters are replaced by the non-coordinating amino acid alanine

Abstract: Nitrogenase MoFe protein (Kp1) from the mutant strain pHK17 or Klebsiella pneumoniae has been purified to give three catalytically active fractions. In this mutant, each of the two bridging cysteine ligands to the P-clusters, alpha-Cys-89 and beta-Cys-94, has been replaced by a non-coordinating residue, alanine. SDS/PAGE and earlier native gels showed that the three fractions retained the normal alpha 2 beta 2 tetrameric form of wild-type Kp1; therefore we conclude that in each of the fractions the subunits ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Purification of the nitrogenase components Kp1 and Cp2 Kp1 was purified from K. pneumoniae strain M5A1 as described previously [25,26]. The specific activity of Kp1 was 1800 nmol of C 2 H 2 reduced min ±1 mg ±1 .…”
Section: Methodsmentioning
confidence: 99%
“…Purification of the nitrogenase components Kp1 and Cp2 Kp1 was purified from K. pneumoniae strain M5A1 as described previously [25,26]. The specific activity of Kp1 was 1800 nmol of C 2 H 2 reduced min ±1 mg ±1 .…”
Section: Methodsmentioning
confidence: 99%
“…The nitrogenase proteins Kp1 and Kp2 were purified from K. pneumoniae to homogeneity as described previously (27,28). In the case of Kp1, this method (27) resolved species containing 1.1 and 1.9 molybdenum atoms per molecule and were shown to be free of any contaminating proteins by SDS gel electrophoresis. The specific activities expressed as nmol of hydrogen evolved/min/mg of protein were as follows: Kp1(1.9 Mo), 2100; Kp1(1.1 Mo), 1100; Kp2, 1399.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Yousafzai et al [31] reported that under the condition of 1 of FeMoco to P-cluster, the EPR intensity (g≈4.30) of Kp1 (MoFe protein of K. pneumonia) was finely proportional to its activity and the metal contents assembled in FeMoco and P-cluster. Zhou et al [17] successfully used the method to verify the model of ΔnifZ Av1 with 2 of FeMoco to P-cluster.…”
Section: Model Of Metalloclusters In Crfe Proteinmentioning
confidence: 98%
“…So calculated values of the activity and metal content for CrFe protein and residual MoFe protein in the preparation according to the EPR intensity can be used to make contrast with and test the experimental results. With the calibration of the residual Mo content suggested above, under the condition that possible FeCrco and P-cluster in CrFe protein are similar in structure and quantity to those of FeMoco and P-cluster in MoFe protein, the EPR-based activity and metal content of CrFe protein and MoFe protein in the preparation are obtained using the method described by Yousafzai et al [31] , as listed in Table 4. The calculated results correspond to the experimental ones well.…”
Section: Model Of Metalloclusters In Crfe Proteinmentioning
confidence: 99%